Smad1 and 5 but Not Smad8 Establish Stem Cell Quiescence Which Is Critical to Transform the Premature Hair Follicle During Morphogenesis Toward the Postnatal State. (13th January 2014) - Kandyba, Eve; Hazen, Virginia M.; Kobielak, Agnieszka; Butler, Samantha J.; Kobielak, Krzysztof
Abstract : Hair follicles (HFs) are regenerative miniorgans that offer a highly informative model system to study the regulatory mechanisms of hair follicle stem cells (hfSCs) homeostasis and differentiation. Bone morphogenetic protein (BMP) signaling is key in both of these processes, governing hfSCs quiescence in the bulge and differentiation of matrix progenitors. However, whether canonical or noncanonical pathways of BMP signaling are responsible for these processes remains unresolved. Here, we conditionally ablated two canonical effectors of BMP signaling, Smad1 and Smad5 during hair morphogenesis and postnatal cycling in mouse skin. Deletion of Smad1 and Smad5 (dKO) in the epidermis during morphogenesis resulted in neonatal lethality with lack of visible whiskers. Interestingly, distinct patterns of phospho-Smads (pSmads) activation were detected with pSmad8 restricted to epidermis and pSmad1 and pSmad5 exclusively activated in HFs. Engraftment of dKO skin revealed retarded hair morphogenesis and failure to differentiate into visible hair. The formation of the prebulge and bulge reservoir for quiescent hfSCs was precluded in dKO HFs which remained in prolonged anagen. Surprisingly, in postnatal telogen HFs, pSmad8 expression was no longer limited to epidermis and was also present in dKO bulge hfSCs and matrix progenitors. Although pSmad8 activity alone could not prevent dKO hfSCs precocious anagen activation, it sustained efficient postnatal differentiation and regeneration of visible hairs. Together, our data suggest a pivotal role for canonical BMP signaling demonstrating distinguished nonoverlapping function of pSmad8 with pSmad1 and pSmad5 in hfSCs regulation and hair morphogenesis but a redundant role in adult hair progenitors differentiation. Stem Cells   2014;32:534–547